2010
DOI: 10.1016/s0873-2159(15)30027-1
|View full text |Cite
|
Sign up to set email alerts
|

Estarão diferentes as pneumonias agudas adquiridas na comunidade com internamento hospitalar em idade pediátrica na última década?

Abstract: The past few years have seen a decline in community acquired pneumonia (CAP) in children in the western world, although this has gone hand-in-hand with more serious cases needing hospital admission. Our study characterises cases of CAP admitted to hospital and compares this data with a 2001 study. We collected data on 63 admissions over a six-month period. The majority were aged 0-2 years old. Chest X-ray showed consolidation/atelectasy in 58 (92.1%) and pleural effusion (PE) in 17 (27.0%), of which 11 were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
5
0
2
Order By: Relevance
“…The 7-valent pneumococcal conjugate vaccine (Prevnar®, PCV-7) became available in Canada in 2000, and was added to the routine Ontario immunization schedule in January 2005 [2]. Introduction of the pneumococcal vaccine has been shown to decrease all-cause radiologic pneumonia admission rates by an average of 27% in children under the age of 5 years [3-10]. …”
Section: Introductionmentioning
confidence: 99%
“…The 7-valent pneumococcal conjugate vaccine (Prevnar®, PCV-7) became available in Canada in 2000, and was added to the routine Ontario immunization schedule in January 2005 [2]. Introduction of the pneumococcal vaccine has been shown to decrease all-cause radiologic pneumonia admission rates by an average of 27% in children under the age of 5 years [3-10]. …”
Section: Introductionmentioning
confidence: 99%
“…( 3 ) In another study, empyema was found in 83 (11%) of 767 children hospitalized with CAP; in comparison with the children with CAP without empyema, those with empyema were older, had longer symptomatic periods, and were more likely to receive nonsteroidal anti-inflammatory drugs. ( 4 ) The objective of the present study was to compare children under 5 years of age with BPP and those with pneumococcal empyema (PE) in terms of their clinical, radiological, and laboratory features.…”
mentioning
confidence: 99%
“…Bacteremic pneumococcal pneumonia (BPP) is considered an advanced stage of severe pneumococcal pneumonia, in which early recognition and appropriate management can have a favorable impact on the outcome. ( 3 ) Given that pleural empyema and BPP are potentially severe, it is important to recognize their clinical peculiarities in order to provide early and appropriate management.…”
mentioning
confidence: 99%
See 2 more Smart Citations